Isomerization mechanism of the HcRed fluorescent protein chromophore - Sun, Qiao; Fischer, Stefan (Physical chemistry, chemical physics, 2012)
To understand how the protein achieves fluorescence, the isomerization mechanism of the HcRed chromophore is studied both under vacuum and in the solvated red fluorescent protein. Quantum mechanical (QM) and quantum mechanical/molecular mechanical (QM/MM) methods are applied both for the ground and the first excited state. The photoinduced processes in the chromophore mainly involve torsions around the imidazolinone-bridge bond (τ) and the phenoxy-bridge bond (φ). Under vacuum, the isomerization of the cis-trans chromophore essentially proceeds by τ twisting, while the radiationless decay requires φ torsion. By contrast, the isomerization of the cis-trans chromophore in HcRed occurs via simultaneous τ and φ twisting. The protein environment significantly reduces the barrier of this hula twist motion compared with vacuum. The excited-state isomerization barrier via the φ rotation of the cis-coplanar conformer in HcRed is computed to be significantly higher than that of the trans-non-coplanar conformer. This is consistent with the experimental observation that the cis-coplanar-conformation of the chromophore is related to the fluorescent properties of HcRed, while the trans-non-planar conformation is weakly fluorescent or non-fluorescent. Our study shows how the protein modifies the isomerization mechanism, notably by interactions involving the nearby residue Ile197, which keeps the chromophore coplanar and blocks the twisting motion that leads to photoinduced radiationless decay.
First published on 18 Jun 2012
Gesehen am 18.06.2018